wp 2015
DOI: 10.24149/wp1506
|View full text |Cite
|
Sign up to set email alerts
|

Non-Renewable Resources, Extraction Technology, and Endogenous Growth

Abstract: We add an extractive sector to an endogenous growth model of expanding varieties and directed technological change. Firms increase their economically extractable stocks of non-renewable resources through R&D investment in extraction technology and reduce their stocks through extraction. We show how the geological distribution of the non-renewable resource interacts with technological change. Our model accommodates long-term trends in non-renewable resource markets -namely stable prices and exponentially increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…One potential possibility is that individuals' increased consumption of products and services necessitates more resources for production and consumption as their wealth increases [43]. Moreover, resource extraction and refining may increase as economies industrialize in tandem with their expansion [44].…”
Section: Resultsmentioning
confidence: 99%
“…One potential possibility is that individuals' increased consumption of products and services necessitates more resources for production and consumption as their wealth increases [43]. Moreover, resource extraction and refining may increase as economies industrialize in tandem with their expansion [44].…”
Section: Resultsmentioning
confidence: 99%
“…A popular theory due to Hotelling (1931) argues that the unexploited metal prices will increase over time with the rate of interest. However, in recent years the Hotelling theory has come under scrutiny and recent research (see, e.g., Anderson et al 2014;Stuermer and Schwerhoff 2015) tends to suggest that the observed patterns of oil production and prices are not compatible with Hotelling's (1931) theory. One of the main reasons for the lack of a positive trend in natural resources is that as reserves are depleted, new reserves are found.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…We exploit a long historical dataset, which partly starts in 1879 and captures a long series of commodity boom and bust periods. We assume that supply elasticities remain constant over time, as technological change offsets the depletion of high quality mineral deposits in line with Stuermer and Schwerhoff (2015).…”
Section: Introductionmentioning
confidence: 99%